(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
This study investigates the adsorption and dissociation mechanism of water molecules on Mn₂O₃ and ZrO₂ surfaces using Density Functional Theory (DFT) within the CP2K computational framework. The aim is to evaluate and compare the catalytic behavior of both oxides toward water splitting for hydrogen production. Results reveal that Mn₂O₃ exhibits higher electronic activity and catalytic efficiency due to its narrower band gap ( 2.1 eV) and the presence of an electronic tail extending up to +0.2 eV above the Fermi level, facilitating local charge transfer to the adsorbed water molecule. Conversely, ZrO₂ possesses greater chemical stability but lower catalytic activity owing to its wider band gap ( 4.8 eV) and the absence of active surface states. The calculated adsorption energies and reaction barriers confirm that Mn₂O₃ offers a more favorable pathway for water dissociation than ZrO₂. The findings suggest that integrating the high catalytic activity of Mn₂O₃ with the chemical stability of ZrO₂ could provide a promising route for designing hybrid catalysts for efficient and sustainable hydrogen generation.